2022
DOI: 10.3390/rs14133140
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Impacts of the 2020 Flood on Crop Production and Food Security in the Middle Reaches of the Yangtze River, China

Abstract: This study uses satellite imagery and geospatial data to examine the impact of floods over the main planting areas for double-cropping rice and grain crops in the middle reaches of the Yangtze River. During summer 2020, a long-lasting 62-day heavy rainfall caused record-breaking floods over large areas of China, especially the Yangtze basin. Through close examination of Sentinel-1/2 satellite imagery and Copernicus Global Land Cover, between July and August 2020, the inundation area reached 21,941 and 23,063 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…In the Yangtze-Huaihe region, the TP concentrations in lakes exhibited a trend of being higher in spring and summer and lower in autumn and winter. This pattern may be related to the double-cropping rice planting system in which fertilisers are applied to the soil during both the spring and summer seasons [54], resulting in a significant inflow of nutrients into lakes [55]. For large lakes, the changing trend in TP concentrations after 2020, characterised by higher levels in summer and autumn and lower levels in spring and winter, is mainly attributed to the time required for the ecological water quality recovery process after the removal of enclosure aquaculture in 2019 [56].…”
Section: Drivers Analysismentioning
confidence: 99%
“…In the Yangtze-Huaihe region, the TP concentrations in lakes exhibited a trend of being higher in spring and summer and lower in autumn and winter. This pattern may be related to the double-cropping rice planting system in which fertilisers are applied to the soil during both the spring and summer seasons [54], resulting in a significant inflow of nutrients into lakes [55]. For large lakes, the changing trend in TP concentrations after 2020, characterised by higher levels in summer and autumn and lower levels in spring and winter, is mainly attributed to the time required for the ecological water quality recovery process after the removal of enclosure aquaculture in 2019 [56].…”
Section: Drivers Analysismentioning
confidence: 99%
“…The high spatial resolution of Sentinel-1 SAR images enables detailed mapping of flood extents, providing valuable information for flood risk management and disaster response efforts. This satellite has been used to detect and map inundation events in various regions around the world, including those affected by monsoon rains and typhoons [5]. The use of Sentinel-1 SAR in flood detection and mapping provides disaster response organizations with the timely and accurate information they need to respond effectively to affected communities [6].…”
Section: Introductionmentioning
confidence: 99%
“…Empirical evidence showed that natural disasters negatively influence agricultural production [ 2 , [7] , [8] , [9] , 12 ]. [ 7 ] found in the Philippines that typhoons significantly decreased production and the losses are estimated at 12.5 million tonnes since 2001 [ 7 ].…”
Section: Introductionmentioning
confidence: 99%